Increased Growth and Production of Chilli (Capsicum Frutescens L.) with The Addition of Biological Organic Fertilizer - Yenisbar; Asmah Yani; Hasni Ruslan; Arief Wicaksono (CIB Nusantara, 2025)
Cayenne pepper (Capsicum frutescens L.) is a high-value horticultural crop, yet its productivity in Indonesia remains below potential despite increasing demand. Biofertilizers provide a sustainable approach to enhancing chili growth and yield, while reducing reliance on chemical fertilizers and preserving soil health. The purpose of this study was to determine the optimal dose and fertilization frequency of Beyonic StarT-mik organic biological fertilizer in enhancing the growth and production of chili (Capsicum frutescens L.). The experiment was conducted from April to December 2020 at the Greenhouse, Faculty of Agriculture, Universitas Nasional, Bambu Kuning, Pasar Minggu, South Jakarta. A factorial Completely Randomized Design (CRD) was employed with two treatment factors, namely fertilizer dose (D0 = control, D1 = 10 ppm, D2 = 20 ppm, D3 = 30 ppm, and D4 = 40 ppm) and fertilizer application frequency (F1 = once a week and F2 = once every two weeks). Observed variables included plant height, stem diameter, dichotomous height, fruit length, fruit diameter, fruit weight per plant, and fruit number per plant. Data were analyzed using analysis of variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that the highest plant height was obtained at a dose of 30 ppm, while the greatest stem diameter and dichotomous height were achieved at 40 ppm with weekly application. Optimal fruit length, diameter, and fruit weight per plant were recorded at a dose of 40 ppm, whereas the highest fruit number and overall yield were observed at 30 ppm, indicating that moderate fertilizer doses are more effective in optimizing chili productivity. This study is essential to establish scientifically sound fertilization strategies, as improper dosage and application frequency of bio-organic fertilizers can reduce yields and hinder sustainable chili production.